AKTUALISASI DIRI SANTRI (PENGURUS) DALAM PEMENUHAN TANGGUNGJAWAB PERSPEKTIF CARL R. ROGERS - Tatimmatul Umah (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2023)
The aim of this research is to determine the forms self actualization of students (management) of the Annuqayah nourth Lubangsa Islamic Boarding School in fulfilling her responsibilities. As well as to find out strategies or obstacles to the self actualization of Islamic boarding school students (administers) Annuqayah nourth Lubangsa Islamic Boarding School in fulfilling her matter. Because it is not uncommon for a student to stiil not be able to realize it potential because there are responsibilities that must be fulfilled. By therefore, this research will reveal how a student can realizing its potential while also having to fulfill it his responsibility. This research uses case study methods and using Carl R. Rogers self actualization theory as a means of analysis. The research subjects consisted of five students, all with backrounds different rear. The research results show that the form self actualization of students (management) in fulfilling their responsibilities based on three aspects of Carl Rogers perspective, namely creativity, feeling freedom, and openness to experience is by attunement the potential of the Islamic boarding school program being implemented. So that can earn plus points, make your self a deadline voluntariliy, not under coercion from others. So that later you will become a person which is always productive and upgrades the potential we have. That is, if today we falled, so tomorrow must be better. While the strategy for self actualization of students (administrators) in fulfilling their responsibilities is by having figures who can be emulated, writing what potential they will achieve in a diary, discipline or commitment in terms of time, doing small things, a supportive environment, and doing responsibilties that he carries out well. And the obstacles to self actualization of students (administrators) in fulfilling their responsibilities are not being able to manage their time, lack of confidence in their potential, not being able to be disciplined in the process of self actualization, not being able to recognize the potential that exists within them, and doubting their potential owned.